The Nordic welfare model in a European perspective - Kuivalainen, Susan; Nelson, Kenneth (Stockholm, 2010)
"Social assistance and minimum income benefits are important indicators for assessing the very basic objective of social policy, namely to mitigate financial hardship and alleviate poverty. The Nordic countries have succeeded well from a comparative point of view in terms of poverty alleviation. However, last-resort safety-nets are changing. Scattered evidence indicate that Nordic social assistance have become less generous. Perhaps are the Nordic countries becoming more similar to the welfare models of Continental Europe or the United Kingdom? This study analyses central dimensions of Nordic social assistance, such as the generosity, scope and effectiveness of benefits. Data for the empirical analyses are from SaMip and LIS. We show that Finland and Sweden, particularly, have suffered from welfare decline, including less generous and effective benefits."